The importance of learning a foreign language from the perspective of tourism industry - Čolić Danijela; Tomić Mladen (University Educons, Faculty of Sports and Tourism, Novi Sad, 2013)
One of the main features of tourism in the second half of the 20th and at the beginning of the 21st century is its mass dimension. The industry of such proportions, accordingly, entails a large number of employees, not only in those branches directly associated with the tourist sector, but also in those that support tourism and create conditions for its development. To provide the best possible service and to keep competitiveness, it is necessary that all tourism workers have certain skills and knowledge and be educated in tourism. One of the indispensible segments of education in tourism and complementary fields is foreign language teaching, due to the important role they play in tourism. Its modelling and strategic planning is conditioned by the economical and sociopolitical fluctuations which change the roles and importance of certain languages in the tourism industry. The object of this paper is the perception of role of foreign languages in tourism and educational processes aimed at tourism industry. The paper primarily concerns the European countries, with an overview of general trends in the tourism industry. The objective of the paper is to address the necessity of acquisition of a greater number of foreign languages, or those languages not adequately represented in the tourism industry, as an important factor of competitiveness in tourism.